2005
DOI: 10.1159/000084807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Calcium Carbonate-Based Dentifrice on in situ Enamel Remineralization

Abstract: This crossover study evaluated the effect of calcium carbonate (CaCO3)-based monofluorophosphate dentifrice on enamel remineralization. Ten volunteers wore palatal appliances containing four enamel blocks with caries-like lesions, two of them covered by a test plaque of mutans streptococci. The following treatments were evaluated: a negative control, a silica-based or a CaCO3-based dentifrice, and the percentage of enamel surface microhardness recovery was determined. The CaCO3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 12 publications
(7 reference statements)
2
25
0
8
Order By: Relevance
“…These calcium carbonate-based dentifrices, unique in Brazil, were tested in vitro (39) and in situ (40), and recently it was demonstrated that calcium carbonate might enhance the effect of fluoride present in the dentifrice (41), probably by its buffering properties and/or enhancement of calcium concentration in plaque (42). Irrespective of the abrasive used, Brazilian fluoride dentifrices have demonstrated ability to interfere with dental caries in in vitro (39,43) and in situ (40,44) studies.…”
Section: Role Of Fluoride Dentifricesmentioning
confidence: 99%
“…These calcium carbonate-based dentifrices, unique in Brazil, were tested in vitro (39) and in situ (40), and recently it was demonstrated that calcium carbonate might enhance the effect of fluoride present in the dentifrice (41), probably by its buffering properties and/or enhancement of calcium concentration in plaque (42). Irrespective of the abrasive used, Brazilian fluoride dentifrices have demonstrated ability to interfere with dental caries in in vitro (39,43) and in situ (40,44) studies.…”
Section: Role Of Fluoride Dentifricesmentioning
confidence: 99%
“…Indeed, using this model it was possible to show the relationship between CaF 2 -like material formed on enamel by professional fluoride application, the release of F to the fluid phase of the test plaque and the consequent reduction of enamel demineralization . Also, this model was successfully used to evaluate the effect of a calcium abrasive-containing F dentifrice on enamel de-and remineralization [Cury et al, 2003[Cury et al, , 2005, and could be used to evaluate under controlled conditions the mechanisms of inhibition of enamel demineralization by F dentifrices.…”
mentioning
confidence: 99%
“…This behavior becomes the surface hardness tests a valid option to evaluate the relationships between fluoride and enamel [23,24].…”
Section: Discussionmentioning
confidence: 99%